A Change or Status Quo? A Critical Analysis of New Core Curricula for Civic Education - Kopińska, Violetta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
In this paper I present the results of research that are focused on the assessment of learning outcomes formulated in “new” core curricula for civic education. Using the results of analysis of “old” core curricula, I look for the answer to the following question: Do the “new” core curricula introduce such changes to civic education that significantly change its shape? In order to answer this question, I analyze in particular the content of the learning outcomes, their structure, taking into account their belonging to the area of knowledge, skills and attitudes. In addition, I assess the learning outcomes for the function of education. I conclude that, despite the changes described, the “new” core curricula retain the status quo in terms of the overall shape of the school civic education and they also repeat the mistakes of the “old” core curricula.